(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The contribution focuses on aspects of detention that affect the body and psyche of the detainee and can therefore fall within the broad scope of bio-law. The finalization of the detention to social rehabilitation influences the law and the practices of management of the prison sentence. The jurisprudence of the European Court of Human Rights addresses several issues that are the subject of individual applications. The subject of each application limits the organicity and completeness of the Court’s case-law (there is no case-law if there are no applications). However, one can find an organic description from the rationes decidendi that justify the case-based outcome of each application.